The impact of listening to english songs on EFL students’ vocabulary acquisition: A literature review - Venna Asyifa Ramadhanti; Farida, Alief Noor (Universitas Negeri Semarang, 2025)
This article explores the impact of listening to English songs on vocabulary learning for English as a Foreign Language (EFL) learners. The primary emphasis is placed on how songs, serving as informal and interactive inputs, assist learners in acquiring vocabulary effortlessly. The article employs a qualitative approach with a systematic literature review with elaborating upon major theories of second language acquisition, including Krashen’s Input Hypothesis, Paivio’s Dual Coding Theory, and Nation’s lexicon learning model, which under describes the role of music-based input in these processes. Learning through songs enhances enjoyment during the recalling process due to colloquial phrases embedded in repetition and rhythm that is easy to memorize. Furthermore, in addition to vocabulary retention, the article also points out the issue of improving students’ learning motivation, pronunciation, and even self-directed learning. With tools like YouTube or Spotify at their disposal, learners can be regularly exposed to the language they are trying to learn. Lastly it shares one of its conclusions: while English songs might appear primarily as entertainment mediums, they can be valuable aids for language acquisition. By bridging theoretical perspectives with practical implications, this article develops useful considerations for educators and researchers regarding the incorporation of music into vocabulary instruction within EFL teaching contexts.